The maker of imaginary worlds: interactive theatre for early years - Patel, Roma (2020)
A young child is competent, capable and a citizen with equal rights to cultural activities. Our fundamental values and attitudes to very young children are the critical determining factors in the quality of their sociocultural lives. Very young children are considered spectators in their own right; however, in the UK there are still only a few theatre performances exclusively made for children under three. This research addresses this issue by investigating the relationship between physical and digital scenography to make Theatre for Early Years (TEY) more interactive and sensory. It begins from a child rights perspective that recognises the child’s voice, perception, perspective, sensory ability. It establishes how a multidisciplinary approach drawing from the fields of Education, Human-Computer Interaction (HCI), and Theatre demands that we rethink our approach to making children’s theatre by establishing a dialogue with our audience and building in interaction from the outset. TEY is an emerging field of practice and research. This thesis focuses on the design and the analysis of interactive scenography for two TEY performances at Lakeside Arts Centre, Nottingham, attended by toddlers and their grown-ups. Multisensory design plays an essential role in TEY because young children predominantly make meaning through directly sensing and interacting with their world. We still have a lot to learn about how children make sense of performances. I argue that embedded digital, tangible, and interactive scenography can create hybrid performances that support agency, play, and real-time interactions in TEY while still serving its purpose as a scenographic element. The design approach considers technologies as both functional and aesthetic, and the scenographic object as a character and audiences as an integral part of the performance. Participatory and interactive experiences afforded by open-source technologies can open up new perceptions, not only in respect to TEY performances but, for the design of flexible, interactive spaces for children’s play